Conceptualization of Metaphor in the MALAKA YouTube Channel: A Cognitive Semantic Study - Aji Permadi; Suhartono (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study is motivated by the importance of metaphors as a cognitive mechanism that helps humans understand abstract concepts through more concrete experiences. In educational discourse, metaphors are often used to facilitate the communication of complex ideas to audiences, including in educational video content. However, research on the conceptualization of metaphors in video media, particularly on educational YouTube channels, remains relatively limited. Therefore, this study aims to uncover the types of structural, orientational, and ontological metaphorical conceptualization in the MALAKA YouTube channel, specifically in the Expert Class segment. This study employs a descriptive research design with a qualitative approach. The data sources consist of eleven videos in the “Expert Class” segment on the MALAKA YouTube channel, while the research data comprises words, phrases, clauses, or sentences containing metaphorical expressions. Data were collected through documentation techniques using the observe-and-record procedure, then analyzed using extralinguistic mapping techniques based on Lakoff and Johnson’s conceptual metaphor theory. The results indicate that metaphor conceptualization on the MALAKA YouTube channel utilizes three types of conceptual metaphors: structural, orientational, and ontological. Structural metaphors exhibit three mapping patterns: journey, illness, and war. Orientational metaphors display top–bottom, front–back, and inside–outside orientations. Meanwhile, ontological metaphors exhibit patterns of personification, reification, and containerization. These findings indicate that metaphors in the MALAKA discourse do not merely function as rhetorical variations but as conceptual mechanisms that help construct an understanding of abstract reality through concrete experiences.